Theatre of Sexual Attraction and Psychological Destruction : The Myth of Hercules and Omphale in the Visual Arts, 1500-1800 - Enenkel, Karl, (Early Modern History and Modern History E-Books Online, Collection 2024., 2025)
The book examines the myth of Hercules and Omphale/Iole which became an important topic in the visual arts, 1500-1800. It offers an analysis of the iconography from the perspective of the history of emotions, classical and Neo-Latin philology, reception and gender studies. The early modern inventions of the myth excel in a skilful display of mixed and compound emotions, such as the male character's psychopathology, and of the theatrical performance of emotions by the female character.